Vesti . Vesti . Herald . Вести - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The Georgian-Abkhazian conflict; the Ukrainian parliament passed a vote of no confidence in the government; the issuing and use of privatization vouchers in Russia; visit of the Austrian deputies to Russia. Contributors: Rostov, IUrii (Anchor) Series description: An information program, produced by the Directorate of Information Programs of the All-Russia State TV Company "Rossiia" [Russia]. It is aired on channel "Rossiia-1" [Russia-1], "RTR-Planeta" [RTR-Planet] and "RTR-Belarus'" [RTR-Belarus].The program was divided into four segments: Sports, Economy, Weather, and Local time. From the mid-1990s the program was broadcasted every 3 hours with a duration of 20 minutes except for the 8 p.m. edition, which lasted 30 minutes. From the end of the 1990s the programwas aired every 3 hours and lasted 30 minutes. Грузино-абхазский конфликт; украинский парламент вынес вотум недоверия правительству; выдача и использование приватизационных чеков в Российской Федерации; визит австрийских депутатов в Россию. Создатели: Ростов, Юрий (Ведущий/Ведущая) Описание серии: Информационная программа, производимая Дирекцией информационных программ Всероссийской Государственной телерадиокомпании "Россия." Выходит в эфир на каналах "Россия-1," "РТР-Планета" и "РТР-Беларусь." Имеет 4 рубрики: 1. Спорт. 2. Экономика. 3. Погода. 4. Местное время. С середины 1990-х годов, передача выходила в эфир каждые 3 часа с хронометражем в 20 минут, С конца 1990-х годов она выходит в эфир каждые 3 часа с хронометражем в 30 минут.